2019
DOI: 10.3389/fchem.2019.00148
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Incorporation of Antimicrobial Plant Phenolics Into Polyolefin-Based Food Contact Materials to Produce Active Packaging by Melt-Blending: Proof of Concept With Isobutyl-4-Hydroxybenzoate

Abstract: There is an increasing interest for active food packaging incorporated with natural antimicrobial agents rather than synthetic preservatives. However, most of plastics for direct contact with food are made of polyolefins, usually processed by extrusion, injection, or blow-molding methods while most of natural antimicrobial molecules are thermolabile compounds (e.g., essential oils). Therefore, addition of plant phenolics (with low volatility) to different polyolefins might be promising to design active control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
10
0
3
Order By: Relevance
“…The results showed a weak antibacterial activity compared to other materials tested in the literature. For example, Cottaz et al [ 37 ] found R values of 1, 4 and 6 for PP, EVA and LLDPE films, respectively, incorporating isobutyl-4-hydroxybenzoate 2% wt/wt. However, increasing the ChNC percentage could improve the antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed a weak antibacterial activity compared to other materials tested in the literature. For example, Cottaz et al [ 37 ] found R values of 1, 4 and 6 for PP, EVA and LLDPE films, respectively, incorporating isobutyl-4-hydroxybenzoate 2% wt/wt. However, increasing the ChNC percentage could improve the antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that pomegranate peel extract kept its antimicrobial activity following extrusion of films. Similarly, Cottaz et al (2019) incorporated a synthetic antimicrobial phenolic, isobutyl-4-hydroxybenzoate in poly(ethylene-co-vinyl acetate; EVA), linear low density polyethylene (LLDPE), and PP by melt-blending to prepare pellets, which were subsequently used to prepare heat-pressed films: all films had an antibacterial activity, demonstrating thus the preservation of isobutyl-4-hydroxybenzoate antibacterial activity after melt processing. Antimicrobial polyphenols, which are less volatile than antimicrobial essential oil components, and which are not denatured by temperatures exceeding 140–150°C like antimicrobial proteins, such as lysozyme, or inactivated by heat, such as antimicrobial peptides like nisin, are thus promising compounds for incorporation in packaging materials elaborated by extrusion.…”
Section: Delivery Modes To Promote the Stability And The Antimicrobial Activity Of Plant Phenolicsmentioning
confidence: 99%
“…Antimicrobial polyolefins are typically blends of polyolefins and antimicrobial agents. 124,125 However, the nonpolar nature of polyolefins accounts for many challenges, including the nonhomogeneous dispersion, agglomeration, and migration of the polar antimicrobial agents to the surface. Cai et al reported the production of functional polyolefins bearing antimicrobial moieties such as quaternary ammonium salts (QASs), imidazolium, and metal ion precursors (copolymer M w up to 38 kg mol −1 ).…”
Section: Biomedical Applicationsmentioning
confidence: 99%